A genealogy of social geomedia: The life, death, and (possible) afterlife of location-based social networks. (November 2022) - Frith, Jordan
In the early 2010s, location-based social networks (LBSNs) received significant attention from both the public and venture capital. The "LBSN moment" was an important period of early mobile geomedia history, and this article argues that the reverberations of that moment still shape the contemporary social geomedia landscape. This article examines the LBSN moment through a media genealogy approach that views the period as a moment of juncture for the development of social location-sharing, which ended up being dominated by large platforms like Facebook and Uber. The article also draws from research on technological development to push back against narratives of inevitability and argue that specific dynamics of the LBSN moment, particularly the double-edged sword of hype, closed-off avenues for the media form. The article ultimately uses an interventionist genealogical approach to explore different paths that could have been—and still could be—taken.